Development and characterization of two cell lines from gills of Atlantic salmon - Gjessing, Mona C. (PLoS One, 2018)
Gill disease in Atlantic salmon, Salmo salar L., causes big losses in the salmon farming industry. Until now, tools to cultivate microorganisms causing gill disease and models to study the gill responses have been lacking. Here we describe the establishment and characterization of two cell lines from the gills of Atlantic salmon. Atlantic salmon gill cell ASG-10 consisted of cells staining for cytokeratin and e-cadherin and with desmosomes as seen by transmission electron microscopy suggesting the cells to be of epithelial origin. These structures were not seen in ASG-13. The cell lines have been maintained for almost 30 passages and both cell lines are fully susceptible to infection by infectious hematopoietic necrosis virus (IHNV), viral hemorrhagic septicemia virus (VHSV), infectious pancreatic necrosis virus (IPNV), Atlantic salmon reovirus TS (TSRV) and Pacific salmon paramyxovirus (PSPV). While infectious salmon anemia virus (ISAV) did not cause visible CPE, immunofluorescent staining revealed a sub-fraction of cells in both the ASG-10 and ASG-13 lines may be permissive to infection. ASG-10 is able to proliferate and migrate to close scratches in the monolayer within seven days in vitro contrary to ASG-13, which does not appear to do have the same proliferative and migratory ability. These cell lines will be useful in studies of gill diseases in Atlantic salmon and may represent an important contribution for alternatives to experimental animals and studies of epithelial–mesenchymal cell biology.